A good global investment for the European Commission: How investing in CGIAR reduces global poverty and benefits E.U. citizens - Hill, Ruth Vargas; Martin, Will; McNamara, Brian; Nia, Reza; Spielman, David J.; Takeshima, Hiroyuki; Vos, Rob (International Food Policy Research Institute, 2025)
CGIAR investments have delivered substantial economic benefits for the E.U. while reducing global poverty and food insecurity. CGIAR has boosted productivity on E.U. farms, expanded export markets, and made food more affordable for E.U. consumers. It has also helped prevent potential damage from pests and diseases that threaten E.U. farm livelihoods. This note quantifies the benefits to farmers, exporters and consumers.